پاکستانی دینی مدارس میں تحقیقی رجحانات: تجزیاتی مطالعہ: Research Trends in Pakistani Religious Seminaries: An Analytical Study (Al-Aasar, 2025)
Well-associated with the legacy of past Islamic scholarship, Madaris in Pakistan have been playing a paramount role to anchoring the society with sacred foundation through knowledge, research and dissemination of religious awareness. The scope of their contributions despite profoundly socio-economic disparities-based society is multi- dimensional such as the scriptural theological; the phenomenological; the spiritual-experiential; the philosophical-conceptual; the socio-cultural; and the historical-political. Madaris globally have been a centre of several discussions in post-9/11 academia examining various aspects such as registration, curriculum, modern education, links with extremism and terrorism, reforms etc. We will study the current research trends conducted within the Madaris highlighting the strengths and weaknesses. Additionally, this is aimed at attempt to highlight the current trends in academia about Madaris. The methodology adopted for this study is qualitative. This study suggests that research conducted in Madaris should focus on how religious discourse in contemporary context tends to keep pace with the changing patterns of society. The paper recommends that although the current research work has enriched our understanding about the current situation of Madaris. It is, however, a complex phenomenon that requires further extensive investigation at micro and macro levels based on practical models that consider the diversity of factors involved impacting the role of Madaris especially in the field of research.  The research concludes that the desired goals can only be achieved through collaborative endeavor from leaders and administrators of Madaris, policy makers, businesses, to government applying divine dynamic and flexible directives together with right policy and procedures.